Mechanosensitivity of the Heart - Kamkin, Andre; Kiseleva, Irina; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book presents the latest findings in field of research of mechanosensitivity of the heart. The Volume focuses on molecular mechanisms of mechanotransduction in cardiac cells. It contains a detailed description of several stretch-induced signaling cascades with multiple levels of crosstalk between different pathways. It highlights the role of cardiac stretch-activated channels and their contribution to cardiac performance. This book provides justification of scientific significance and potential for clinical applications of findings of fundamental investigations in the field of mechanosensitivity, which is stressed by description of reported increased sensitivity of cardiac cells to mechanical stress under various pathological conditions. It contains new insights into mechanoelectrical feedback on the level of the whole heart and results of experimental investigations of electromechanical properties of cardiac tissue. This book is a unique collection of reviews outlining current knowledge and future developments in this rapidly growing field. Currently, investigations of the effects of mechanical stress on the heart are focused on several issues. The majority of studies investigate the effects of mechanical stimulation on mechanosensitive channels, as its primary target and interactive agent, and aim on description of downstream intracellular signaling pathways together with addressing general issues of biomechanics of the heart. Knowledge of biomechanics, and mechanisms which underlie it on molecular, cellular, tissue, organ and organism, is necessary for understanding of the normal functioning of living organisms and allows to predict changes, which arise due to alterations of their environment, and possibly will allow to develop new methods of artificial intervention. The book brings up the problem closer to the experts in related medical and biological sciences as well as practicing doctors besides just presenting the latest achievements in the field.
Molecular Mechanisms of Mechanotransduction in Cardiac Cells -- Titin and Titin-Associated Proteins in Myocardial Stress-Sensing and Mechanical Dysfunction -- Mechanical Stretch-Induced Reorganization of the Cytoskeleton and the Small GTPase Rac-1 in Cardiac Fibroblasts -- Molecular Signaling Mechanisms of Myocardial Stretch: Implications for Heart Disease -- Mechanical Stress Induces Cardiomyocyte Hypertrophy Through Agonist-Independent Activation of Angiotensin II Type 1 Receptor -- Mechanically Induced Potentials and Currents of the Cardiac Cells in Healthy and Diseased Myocardium -- Mechanostransduction in Cardiac and Stem-Cell Derived Cardiac Cells -- Stretch-Activated Channels in the Heart: Contribution to Cardiac Performance -- Effects of Applied Stretch on Native and Recombinant Cardiac Na+ Currents -- Mechanosensitive Alterations of Action Potentials and Membrane Currents in Healthy and Diseased Cardiomyocytes: Cardiac Tissue and Isolated Cell -- The Role of Mechanosensitive Fibroblasts in the Heart: Evidence from Acutely Isolated Single Cells, Cultured Cells and from Intracellular Microelectrode Recordings on Multicellular Preparations from Healthy and Diseased Cardiac Tissue -- Scanning Ion Conductance Microscopy for Imaging and Mechanosensitive Activation of Selected Areas of Live Cells -- Mechano-Electric Feedback in the Whole Heart and a Computer Simulation Study -- The Contribution of MEF to Electrical Heterogeneity and Arrhythmogenesis -- Mechanical Modulation of a Reentrant Arrhythmia: The Atrial Flutter Case -- Early Hypertrophic Signals After Myocardial Stretch. Role of Reactive Oxygen Species and the Sodium/Hydrogen Exchanger -- Stretch-Induced Inotropy in Atrial and Ventricular Myocardium -- Effects of Wall Stress on the Dynamics of Ventricular Fibrillation: A Computer Simulation Study of Mechanoelectric Feedback -- Electromechanical Modelling of Cardiac Tissue -- Arteries as a Source of Myogenic Contractile Activity: Ionic Mechanisms -- Specific Mechanotransduction Signaling Involved in Myogenic Responses of the Cerebral Arteries.
Keywords: Medicine; Human physiology; Cardiology; Biochemistry; Cytology; Biomedicine; Biomedicine general; Cell Biology; Medical Biochemistry; Human Physiology; Cardiology